The Role of Apelins in the Physiology of the Heart - Aydin, Suna; Eren, Mehmet Nesimi; Sahin, Ibrahim; Aydin, Suleyman (Bentham Science Publ Ltd, 2014)
Apelins are a peptide hormone known as the ligand for the G protein-coupled APJ receptor. There are many different forms of apelin in the circulation. Apelins and their receptors are expressed in the central nervous system, including the hypothalamus, and in numerous other peripheral tissues. These peptides are also synthesized in and secreted from the adipose tissues. Additionally, apelins were immunohistochemically shown to be synthesized in smooth muscle cells in the media of the left internal mammary artery (LIMA) and the saphenous vein, fibroblast cells in the media of the aorta and endothelial cells of the intima. Similarly, it was recently reported that the enzyme linked immunoassay (ELISA) measurements of apelins were similar to its immunohistochemical data in the tissues of the aorta and left internal mammary artery. Apelins which are rapidly eliminated from the circulation have a half life of less than eight minutes. The normal concentration of apelins in the human plasma ranges between 1.3 ng/mL and 246 +/- 0.045 ng/mL. Apelins serve important functions in food intake, vasopressin (anti-diuretic hormone: ADH) and histamine release, gastric acid, bicarbonate secretion and insulin secretion, diuresis, cell proliferation, angiogenesis, glucose-fluid balance and regulation of gastrointestinal motility and cardiovascular system. Therefore, this review aims to focus on the potential role of the apelin system in the balance of the cardiovascular system.
Keywords: Apelins; cardiovascular system; fluid homeostasis; peptides